The Cost of Populism in Argentina, 2003-2015 - Cachanosky, Nicolas (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2018)
This paper studies the historical context, and economic and institutional impact of the Néstor Kirchner’s and Cristina Fernández de Kirchner’s presidencies (Kirchner-Kirchner administration) in Argentina. The effects of the major economic policies during their presidency are explained as well as the indices fall of the institutional quality. The challenges of stepping out of populism are also mentioned.